Perancangan Platfrom Berbasis E-Commerce untuk Mendukung UMKM Rumahan di Pasaman Barat - afwana, afwana; Annas, firdaus; fitriani, nita (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The following paragraphs have been developed: This research not only focuses on the implementation of e-commerce platforms for MSMEs in West Pasaman, but can also serve as a model for the development of similar platforms in various developing countries. By customising the features of the platform based on the needs and digital infrastructure of each region, this model has the potential to help improve the competitiveness of MSMEs globally. The scalability of the platform is an important factor in ensuring widespread adoption and its impact on digital economic growth. Therefore, further research can be conducted by analysing the effectiveness of similar platforms in different countries to identify best practices in supporting MSMEs. In addition, it is important to explore the extent to which this model can be applied in different markets with different conditions, including in countries that have limitations in digital infrastructure. Platform adaptation should consider factors such as business culture, e-commerce regulations, and the digital readiness of local MSMEs. Furthermore, the impact of e-commerce platforms on the local economy also needs to be scrutinised, especially in improving global market access for MSMEs and accelerating local product exports. Digital security and regulatory aspects are a challenge in the implementation of cross-border e-commerce platforms. Data protection, online transaction security, and compliance with international regulations must be considered for these platforms to operate sustainably. With a broader approach, this research can contribute to developing e-commerce solutions that not only have an impact at the local level, but can also become a global reference for the growth of MSMEs in the digital era.